Physiologically Based Pharmacokinetic and Physiologically Based Biopharmaceutic models research in Latin America: A regional level bibliometric analysis, 2011-2023 - Marx Ribeiro; Juliana Cordeiro Cardoso; José Eduardo Severino Martins; Aline Ferreira Pinto; Eliana Maria Barbosa Souto; Patricia Severino (Brazilian Journal of Pharmaceutical Sciences)
Abstract The landscape of scientific research in Latin America (LA), particularly in the realms of the Physiologically Based Pharmacokinetic (PBPK) and Physiologically Based Biopharmaceutic models (PBPM), is a mosaic of varied contributions, collaborations, and specializations. This study examines research production in the region using data from the Scopus and PubMed databases collected between 2011 and 2023. Brazil stands out as a prominent country in terms of the quantity of publications. When considering thematic specialization, Colombia cones first as the country with the greatest Relative Specialization Index (RSI), followed by Brazil, Cuba, Uruguay, Mexico, and Argentina. Regarding internationalization, Brazil and Mexico are currently exerting significant influence, particularly through their increasing cooperation with the United States and Europe. Interestingly, there is a lack of cooperation inside Latin America at the regional level. Regarding the contribution of Latin-American institutions, the State University of Maringá leads in number of publications, followed by the University of São Paulo and the Federal University of São Paulo. In this work, we analyzed the strengths and weaknesses of LA’s scientific contributions, offering a roadmap for future collaborative and specialized efforts in the field of PBPK and PBBM.